Avaliação anátomo-clínica do dantroleno sódico no trauma medular agudo experimental em ratos por período prolongado - Paula Mayer Costa (2010)
The aim of the present study was to evaluate for a long period the effect of a single dose of dantrolene sodium in the treatment of rats subjected to acute spinal cord injury. Therefore, 21 Rattus norvegicus were equally distributed into three groups. In G1, the negative control group, the animals were submitted to dorsal laminectomy of the T13 vertebra and received the diluent of the drug intraperitoneally (IP). In the other groups, in addition to laminectomy, the animals were subjected to compressive spinal cord injury (SCI). G2, the positive control group, received the diluent for the drug, and G3, 10mg/kg of dantrolene sodium, both intraperitoneally in a single dose, one hour after the SCI. The animals were clinically evaluated using the following tests: deambulation in open field (BBB test) and beam walking test (motor capacity), pain sensitivity (PS), proprioceptive (PP) and tactile positioning (PT), and inclined plane (IP). The animals were euthanized 31 days after injury and the spinal cords were collected. Sections cranial and caudal to the epicenter were obtained for morphological (HE) evaluation, and cranial sections, for immunohistochemical staining with Anti-NeuN antibody. The G3 had earlier clinical recovery determined by the tests BBB, motor capacity, PS, and IP as compared to G2, due to increased neuronal integrity observed in the morphology and the greater amount of intact neurons stained with Anti-NeuN antibody. Concluding, dantrolene sodium, in a single intraperitoneal administration, at a dose of 10 mg/kg, reduced the severity of injuries triggered by acute spinal cord injury and preserves neuronal integrity at 30 days post-trauma.